PROGRAMMING ANDROID WITH KOTLIN achieving structured concurrency with coroutines - LAURENCE, PIERRE-OLIVIER (O'REILLY MEDIA, 2021)
Developing applications for the Android mobile operating system can seem daunting, particularly if it requires learning a new programming language: Kotlin, now Android?́?s officialdevelopment language. With this practical book, Android developers will learn how to make the transition from Java to Kotlin, including how Kotlin provides a true advantage for gaining control over asynchronous computations. Authors Pierre-Olivier Laurence, Amanda Hinchman-Dominguez, G. Blake Meike, and Mike Dunn explore implementations of the most common tasks in native Android development, and show you how Kotlin can help you solve concurrency problems. With a focus on structured concurrency, a new asynchronous programming paradigm, this book will guide you through one of Kotlin's most powerful constructs, coroutines. Learn about Kotlin essentials and the Kotlin Collections Framework Explore Android fundamentals: the operating system and the application container and its components Learn about thread safety and how to handle concurrency Write sequential, asynchronous work at a low cost Examine structured concurrency with coroutines, and learn how channels make coroutines communicate Learn how to use flows for asynchronous data processing Understand performance considerations using Android profiling tools Use performance optimizations to trim resource consumption.
Keywords: Android (Electronic resource); Application software -- Development; Smartphones -- Programming; Programming languages (Electronic computers); Logiciels d'application; Développement; Téléphones intelligents; Programmation; Application software; Development